Rapid purification and crystallization of Neurospora crassa tyrosinase - A. M. Fuentes; M. A. J. Taylor; J. Jenkins; I Connerton (Fungal Genetics Reports, 1993)
A rapid method for the purification of Neurospora crassa tyrosinase (EC 1.14.18.1) has been developed using an FPLC system that yields sufficient pure protein for protein crystals to be grown.